The journey of aromatic rice: genetic diversity, global trade, and prospects for improvement: a review : The Journey of aromatic rice - Islam, Mohaimin; Akter , Nasrin Akter; Islam, Nur; Hasan, Nahid; Patwary, Azmia; Khatun, Sumaya; Maniruzzaman, Skeikh; Ali, Liakat (Annals of Bangladesh Agriculture, 2026)
Aromatic rice, a globally esteemed crop, holds significant cultural and economic value due to its unique fragrance and delicate flavor. Originating in the Indian subcontinent around 400 BC, now grown in over 30 countries. Its evolution is hypothesized to have resulted from hybridization between newly introduced japonica rice, carrying the betaine aldehyde dehydrogenase 2 (BADH2) aroma mutation, and local Aus varieties. This market, dominated by Basmati and Jasmine types, constitutes 15-18% of the global rice trade and commands a significantly higher market value than non-aromatic rice. The distinctive aroma is primarily attributed to 2-acetyl-1-pyrroline (2-AP) alongside over 300-500 other volatile compounds, whose synthesis is regulated by BADH2, a recessive gene on chromosome 8. While BADH2 is a key driver, minor quantitative trait loci (QTLs) and other genes contribute to aroma complexity, revealing its polygenicity. Conventional breeding has developed prominent cultivars like Pusa Basmati-1of India and KDML105 of Thailand. Recently, Marker aided selection (MAS) has facilitated the precise introgression of aroma genes into high-yielding, non-aromatic backgrounds, evading the limitations of traditional phenotyping. The expanding global market for aromatic rice, driven by consumer preference for premium quality and rising demand, necessitates continued improvement. Recent innovations in genomics and genome editing technologies will offer unprecedented precision for genetic alterations of aroma. This review highlights the evolutionary history, genetic basis, global market dynamics, and breeding advancements in aromatic rice, emphasizing the need for continued exploration of its rich genetic diversity to ensure sustainable production and enduring international appeal. Ann. Bangladesh Agric. 29(2): 265-290